A metaficção no fazer literário de Lygia Bojunga: projeto de escrita de uma autora - Patrocinio, Gabriela Trevizo Gamboni (2020)
This thesis aims to investigate the self-referentiality in the works Intramuros (2016), Retratos de Carolina (2002) and Fazendo Ana Paz (1991), by Lygia Bojunga, in an attempt to establish their correlations regarding the use of metafictional strategies, a trend that is expressive in the literature contemporary youth. In addition to identifying such strategies, we aim to reflect on self-referentiality as a motivator and instigator of a more reflective and critical reader, given that, when faced with metafictional narratives, this reader will not only be a mere consumer, but rather, a collaborator in the construction of these narratives. The participation of the reader in this (re) construction of the literary text turns out to be an invitation to experience the backstage of artistic production, inciting him to become more reflective and to perform a less naive reading. The research is divided into three chapters. The first chapter develops a brief historical retrospective, seeking to go back to the roots of Brazilian youth Literature, its tendencies and the unfolding of metafiction, including several authors and works, in particular, Lygia Bojunga. In the second chapter, we present the concept of metafiction, starting from theorists such as Linda Hutcheon, Patricia Waugh, Gustavo Bernardo and Diana Klinger. Then, we analyze the three works, from the metafictional bias that the author uses in her narrative constructions, signaling the peculiarities existing in each one of them. In Fazendo Ana Paz, we analyze the weaving of the characters, highlighting the way the author denounces her writing; in Retratos de Carolina, we highlight the role of the author to appear as a character and the resources used in the construction of the work; finally, in Intramuros, we unveiled the increasing complexity of the resources employed by Bojunga, revealing the recurrence of self-fictional procedures in the elaboration of his plot, marked by a theatrical character. Finally, in the third chapter, we focus on the writer's literary aesthetic project, showing how the metafictional strategies that are worth suggest - and even demand - a reader who is provoked and summoned to abandon his alienated and controlled position, and is led to discover meanings, requiring a more critical and participative awareness of challenging fictional formations, which suggest new ways of reading the text and the world. This chapter, in particular, is based on Wolfgang Iser and Teresa Colomer. At the end, we present some considerations that point to the results found, as well as the references used in this investigation